Fiscal Equity and America's Community Colleges. (2nd January 2019) - Kolbe, Tammy; Baker, Bruce D.
ABSTRACT: Community colleges play an increasingly important role in the higher education landscape. Yet, what is unclear is whether existing models for funding community colleges are up to the task of preserving, or even expanding, access to postsecondary education, particularly among groups historically underrepresented in higher education. Of particular concern has been whether existing resources are distributed among colleges in a fair and efficient manner. In this article, we use frameworks and policy templates from K-12 education finance to better understand differences in resources available to community colleges nationwide, prior to and after the 2008 recession. Specifically, we evaluate the extent of variation in per pupil spending within states; the extent to which variation is associated with community wealth, a proxy for student need; and whether state appropriations, as a share of total revenue, substantively impact fiscal equity. Taken together, we find substantial differences in spending among community colleges within states; evidence that spending differences may be related to proxies for student need; and that changes in state appropriations impact fiscal equity across community colleges.